HISTORY OF PUBLIC SCHOOL EDUCATION (VOLKSCHOOL) IN THE DUTCH COLONIAL PERIOD IN ACEH - Fika Ardhillah; Ajidar Matsyah; Muhammad Yunus Ahmad (Indonesian Journal of Islamic History and Culture, 2022)
One of the three-year Dutch schools in Aceh is called People's School (Volkschool). Starting with the few Acehnese who are aware that there were once schools built by Dutch colonialists in Aceh before the foundation of schools as they are now. Because the history of the People's School (Volkschool) is not widely known among Acehnese, it makes for a very fascinating study subject. The purpose of this study is to understand more about how the People's School (Volkschool) in Aceh was founded and how its educational system operated during the Dutch colonial era. By using library research methods (Library Research) and oral sources (interviews). This study uses historical research methods, namely heuristics (data collection), source criticism (data verification), interpretation (data analysis), and historiography. The results showed that the first People's school (Volkschool) was formed in Aceh on December 30, 1907 in Ulee Lheu. This was motivated by the Dutch goal of realizing the desire of the Dutch East Indies government to spread education as widely as possible at the lowest possible cost. the three years of instruction at the People's School (Volkschool). The reading, writing, and math components of the Volkschool curriculum are its format. The Dutch colonialists paid for the classroom supplies, including slate and grip writing implements. Parents of pupils are required to cover expenses ranging from 10 cents to 15 cents. No fees were ever taken from pupils, not even in the early years of the school's existence or towards the conclusion of the colonial era. The Acehnese may be employed by the Dutch colonialists even though the wages were extremely poor after receiving an education at this institution. Although the Dutch colonialists initially forced the people of Aceh to send their children to the People's School (Volkschool), this compulsion ultimately led to exceptional outcomes. Where the people of Aceh may produce an enlightened generation like the one we have today and are no longer illiterate in Latin.